Livelihood Interest Groups for sustainable initiatives - Verzola, Leonora K. (Technical Centre for Agricultural and Rural Cooperation, 2018)
The Livelihood Assistance Fund (LAF) is a major intervention of the Second Cordillera Highland Agriculture Resource Management (CHARMP2) project – a seven-year initiative of the Philippines Department of Agriculture. After 7 years of implementation, CHARMP2 was extended for one year and upscaled for two more years. LAF provides start-up capital to farmer groups to enable them to initiate group businesses. After LAF had been running for two years the team planned to see if the Livelihood Interest Groups (LIGs) had had valuable experiences. Respondents were able to identify many strengths and weaknesses, demonstrating that LIGs were able to generate considerable experience in implementing their LAF-funded group businesses, and that these experiences could be used in upscaling CHARMP2 and similar livelihood projects.